THE RESPONSE OF HYBRID CATFISH FRY AND FINGERLINGS TO TWO NON EXTRUDED FLOATING FEED - OVIE S. O; IBIYO, L. M. O.; BABALOLA, T. O. O.; EZE, S. S. (Nigerian Journal of Fisheries, 2012)
Hybrid of male Heterobranchus longifilis and female of Clarias gariepinus, fry (0.87 ± 0.02 g) and fingerlings (4.42 ± 0.02 g) were stocked 10 fish and 7 fish respectively in 30 litres of water in 54 litre capacity aquaria in triplicates. Two NIFFR floating feed (42.01% C. P., and 44.75% C. P.) were formulated and fed to the fish in triplicates for 56 days. There was no significant variation (P > 0.05) in the mean weight gain, protein efficiency ratio, food conversion ratio and specific growth rate of fish fed the various diets. The Feed Conversion Ratio (FCR) and Specific Growth Rate (SGR) were highest in fry than in the fingerlings that were fed with NIFFR diets. The Protein Efficiency Ratio (PER) was best for juveniles than for fingerlings and fry. The condition factor of the fry, fingerlings and juveniles fed the various diets was less than 1 while the regression coefficient (r2 ) was 1 for the various treatments in the three experiments. Carcass composition showed that moisture content was higher at stocking than at harvest while all other parameters were higher at harvest than at stocking.